2017
DOI: 10.1177/0706743717727243
|View full text |Cite
|
Sign up to set email alerts
|

Depression Screening and Health Outcomes in Children and Adolescents: A Systematic Review

Abstract: There is no direct RCT evidence that supports depression screening among children and adolescents. Groups that consider recommending screening should carefully consider potential harms, as well as the use of scarce health resources, that would occur with the implementation of screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…However according to a systematic review by Roseman et al ., there is no major benefit of screening for depression among adolescents, which will have to be undertaken after weighing the benefits and harm specific to a particular population and geo-cultural situation. [15]…”
Section: Discussionmentioning
confidence: 99%
“…However according to a systematic review by Roseman et al ., there is no major benefit of screening for depression among adolescents, which will have to be undertaken after weighing the benefits and harm specific to a particular population and geo-cultural situation. [15]…”
Section: Discussionmentioning
confidence: 99%
“…However, screening for depression is only useful when it improves outcomes beyond those of standard care (14)(15)(16). For example, a 2017 systematic review of the clinical trial evidence for depression screening among children and adolescents (17) found no direct randomized control trials (RCTs) evidence to support it. The researchers noted there would be unintended harm from screening and recommended that there should be careful consideration "of potential harms, as well as the use of scarce health resources, that would occur with the implementation of screening programs" [(17), p. 813].…”
Section: Depression Screening In Adolescents: Is There Evidence Of Bementioning
confidence: 99%
“…Additionally, an examination of recommendations from three national guideline organizations (17) revealed a lack of evidence to support questionnaire-based screening. The recommendations for screening for alcohol misuse, depression, developmental or speech and language delays, domestic violence, and suicide risk from the United States Preventive Services Taskforce (USPSTF), the Canadian Task Force on Preventative Health Care (CTFPHC), and the United Kingdom National Screening Committee (UKNSC) were reviewed.…”
Section: Depression Screening In Adolescents: Is There Evidence Of Bementioning
confidence: 99%
“…Usually, depression screening uses a preset threshold to identify the severity of state status [ 19 ]. Previous articles reported several self-rated measures to identify the depressive symptoms with full confidence [ 19 , 25 , 30 , 31 ] but no clinical interviews being referred to support the diagnosis, the rate of misjudgment was quite high [ 32 , 33 ]. On the base of the Kutcher Adolescent Depression Scale, Beck Depression Inventory (BDI), and Hamilton rating scale for depression [ 3 , 34 , 35 , 36 ], we established a self-rate measure to assess the adolescent depressive prodrome [ 36 , 37 ], which evolves 16 depressive symptoms defined by DSM-5 with a 4-point scale and ranged total manifestation scores from 16–64 [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%